Knowledge, Curiosity, Communication Channels and Panic during COVID-19 Movement Control Order - Ali Salman (International Journal of Media and Communication Research, 2021)
Media and Communication Channels as carriers of news on COVID-19 might have a role in spreading panic among the population. This study was conducted to determine the media and communication channels responsible for creating panic among Malaysians during COVID-19 Movement Control Order (MCO). A survey using questionnaire was used to collect data from 253 respondents across Malaysia. In terms of media and communication channels, most of the respondents reported that they panic due to the exposure to reports from online media (Internet and social media). This is followed by communication with family members. TV, radio and newspaper reports are the third contributors of panic among Malaysians during COVID-19 MCO. Meanwhile about half of the respondents said they panic because of curiosity about COVID-19. It is an irony that online media, which contributes to the panic is also a source of information on COVID-19 and platform to work from home.